Job Satisfaction Drivers in Public Institutions: Evidence from Balikpapan’s Tourism Office - Didik Hadiyatno (Fakultas Ekonomi Universitas Kadiri, 2026)
This study investigates the determinants of employee satisfaction within a public sector institution in an emerging economy context, focusing on the Department of Youth, Sports, and Tourism in Balikpapan, Indonesia. Specifically, it examines the influence of motivation, work environment, and work discipline on employee satisfaction. Employing a quantitative approach, the research surveyed the entire population of 46 civil servants using a census method. Data were collected through observation, structured interviews, and standardized questionnaires, then analyzed using multiple linear regression with SmartPLS software. The findings reveal that both motivation and work environment have a positive and significant impact on employee satisfaction, indicating that intrinsic and extrinsic motivational factors as well as conducive workplace conditions are critical to enhancing job fulfillment in public institutions. Conversely, work discipline shows a negative and statistically insignificant effect on employee satisfaction, suggesting that disciplinary measures alone may not contribute meaningfully to job satisfaction without complementary motivational and environmental support. These results provide empirical insights for human resource management practices in local government agencies, particularly in the context of developing regions. The study contributes to the literature on public administration and organizational behavior by highlighting context-specific factors influencing employee well-being in the public sector.